2015
DOI: 10.1111/jace.13638
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Processing for Improved Ionic Conductivity in Li2O–Al2O3–TiO2–P2O5 Glass‐Ceramics

Abstract: Li1.4Al0.4Ti1.6(PO4)3 (LATP) was synthesized using a glass‐ceramics approach through crystallization in a conventional box furnace and a modified microwave furnace. The microstructure of samples that were microwave processed at 1000°C showed a larger average grain size (0.87 μm) when compared with the grain size of conventionally processed samples (0.30 μm) at the same temperature. Microwave processing led to significant enhancement of the conductivity when compared with conventional processing for all crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In solid-based approaches, Davis and Nino [65] demonstrated that LATP synthesized through aM W-assisted method had an ionic conductivity of 5.33 10 À4 Scm À1 ,w hich was5 times higher than that of LATP obtained through conventional heat treatment. They attributed the Li-ion conductivity enhancement to differences in the microstructure, specifically the larger grain size and lower grain boundary resistance.…”
Section: Sinteringp Arametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In solid-based approaches, Davis and Nino [65] demonstrated that LATP synthesized through aM W-assisted method had an ionic conductivity of 5.33 10 À4 Scm À1 ,w hich was5 times higher than that of LATP obtained through conventional heat treatment. They attributed the Li-ion conductivity enhancement to differences in the microstructure, specifically the larger grain size and lower grain boundary resistance.…”
Section: Sinteringp Arametersmentioning
confidence: 99%
“…To reducel ithium loss during the heat-treatmentp rocess for LATP and LAGP solid electrolyte synthesis, rapid sintering techniques have been developed:S PS, [60][61][62] FAST, [63] and MW-assisted sintering (Figure1c-e). [64,65] In principle, the SPS technique utilizes electrical currents to aid densification in ad ie with resistive heating at highr ates (> 100 8Cmin À1 ). [66,67] FAST applies av oltage exclusively to the sample during sintering to increase the resistivity of the material and then achieveasimilare ffect to that of solid-state sintering.…”
Section: Fast Sintering Techniquesmentioning
confidence: 99%
“…The atomic ratio of Y, Zr, P, and O is summarized in Table S1 in the Supporting Information, and based on the ratio, the x value in Li 1+ x Y x Zr 2− x (PO 4 ) 3 is estimated to be x ≈0.11. The conductivity of the membrane was estimated by fitting the electrochemical impedance spectrum (Figure c) with an equivalent circuit shown in Figure S4 in the Supporting Information according to a recent relevant study of the solid state electrolyte . At 25 °C, the optimized conductivity of the LYZP membrane was ≈2.5 × 10 −5 S cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Since Li is not detectable with the EDS, the map ping of Li is not provided in Figure S2 in the Supporting Infor mation. [9] At 25 °C, the optimized conductivity of the LYZP membrane was ≈2.5 × 10 −5 S cm −1 . The atomic ratio of Y, Zr, P, and O is summarized in Table S1 in the Supporting Informa tion, and based on the ratio, the x value in Li 1+x Y x Zr 2−x (PO 4 ) 3 is estimated to be x ≈0.11.…”
Section: Characteristics and Properties Of The Lyzp Solid-electrolytementioning
confidence: 96%
“…The following supporting information can be downloaded at: , Table S1: Comparison of ionic conductivities and activation energies of various solid electrolytes. References [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%